Global sensitivities of reactive N and S gas and particle concentrations and deposition to precursor emissions reductions - Y. Ge; Y. Ge; Y. Ge; M. Vieno; D. S. Stevenson; P. Wind; M. R. Heal (Atmospheric Chemistry and Physics, 2023)
The reduction of fine particles (PM2.5) and reactive N (Nr) and S (Sr) species is a key objective for air pollution control policies because of their major adverse effects on human health, ecosystem diversity, and climate. The sensitivity of global and regional Nr, Sr, and PM2.5 to 20 % and 40 % individual and collective reductions in anthropogenic emissions of NH3, NOx, and SOx (with respect to a 2015 baseline) is investigated using the EMEP MSC-W (European Monitoring and Evaluation Programme Meteorological Synthesizing Centre – West) atmospheric chemistry transport model with WRF (Weather Research and Forecasting) meteorology. Regional comparisons reveal that the individual emissions reduction has multiple co-benefits and small disbenefits on different species, and those effects are highly geographically variable. A 40 % NH3 emission reduction decreases regional average NH3 concentrations by 47 %–49 % but only decreases NH<msubsup>4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="9ae7496f73369cba691a3bcfb358d1a5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6083-2023-ie00001.svg" width="8pt" height="15pt" src="acp-23-6083-2023-ie00001.png"/></svg:svg> by 18 % in Euro_Medi, 15 % in East Asia, 12 % in North America, and 4 % in South Asia. This order follows the regional ammonia richness. A disbenefit is the increased SO2 concentrations in these regions (10 %–16 % for 40 % reductions) because reduced NH3 levels decrease SO2 deposition through altering atmospheric acidity. A 40 % NOx emission reduction reduces NOx concentrations in East Asia by 45 %, Euro_Medi and North America by ∼ 38 %, and South Asia by 22 %, whilst the regional order is reversed for fine NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="01db1dfc152077444e810c7eff7103ec"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6083-2023-ie00002.svg" width="9pt" height="16pt" src="acp-23-6083-2023-ie00002.png"/></svg:svg>, which is related to enhanced O3 levels in East Asia (and also, but by less, in Euro_Medi) and decreased O3 levels in South Asia (and also, but by less, in North America). Consequently, the oxidation of NOx to NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="d4917cb251612ae03efebb0a66479930"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6083-2023-ie00003.svg" width="9pt" height="16pt" src="acp-23-6083-2023-ie00003.png"/></svg:svg> and of SO2 to SO<msubsup>42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="820c2a883eb6831c3f3dfbf9fe5018ac"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6083-2023-ie00004.svg" width="13pt" height="17pt" src="acp-23-6083-2023-ie00004.png"/></svg:svg> is enhanced in East Asia but decreased in South Asia, which causes a less effective decrease in NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="d96e0e0e6a6172a7d34ac185b1d0a8a7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6083-2023-ie00005.svg" width="9pt" height="16pt" src="acp-23-6083-2023-ie00005.png"/></svg:svg> and even an increase in SO<msubsup>42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="400cdf836a92a8210fecc81dc876b9d6"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6083-2023-ie00006.svg" width="13pt" height="17pt" src="acp-23-6083-2023-ie00006.png"/></svg:svg> in East Asia but quite the opposite in South Asia. For regional policy making, it is thus vital to reduce three precursors together to minimize such adverse effects. A 40 % SOx emission reduction is slightly more effective in reducing SO2 (42 %–45 %) than SO<msubsup>42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="5c032620c8f70b9e15908a9c5486e9a8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6083-2023-ie00007.svg" width="13pt" height="17pt" src="acp-23-6083-2023-ie00007.png"/></svg:svg> (34 %–38 %), whilst the disbenefit is that it yields a ∼ 12 % increase in total NH3 deposition in the four regions, which further threatens ecosystem diversity. This work also highlights important messages for policy makers concerning the mitigation of PM2.5. More emissions controls focusing on NH3 and NOx are necessary for regions with better air quality, such as northern Europe and eastern North America. In East Asia, the three individual reductions are equally effective, whilst in South Asia only SOx reduction is currently effective. The geographically varying non-one-to-one proportionality of chemical responses of Nr, Sr, and PM2.5 to emissions reductions revealed by this work show the importance of both prioritizing emissions strategies in different regions and combining several precursor reductions together to maximize the policy effectiveness.